Predicting the crystal structure of $$\hbox {N}_5\hbox {AsF}_6$$ high energy density material using ab initio evolutionary algorithms - Benchafia, El Mostafa; Wang, Xianqin; Iqbal, Zafar; Abedrabbo, Sufian (Scientific reports, 2021)
$$\hbox {N}_5\hbox {AsF}_6$$ N 5 AsF 6 is the first successfully synthesized salt that has a polymeric nitrogen moeity ( $$\hbox {N}_5^+$$ N 5 + ). Although 12 other $$\hbox {N}_5^+$$ N 5 + salts followed, with $$\hbox {N}_5\hbox {SbF}_6$$ N 5 SbF 6 and $$\hbox {N}_5\hbox {Sb}_2\hbox {F}_{11}$$ N 5 Sb 2 F 11 being the most stable, the crystal structure of $$\hbox {N}_5\hbox {AsF}_6$$ N 5 AsF 6 remains unknown. Currently, it is impossible to experimentally determine the structures of $$\hbox {N}_5\hbox {AsF}_6$$ N 5 AsF 6 due to its marginal stability and explosive nature. Here, following an ab initio evolutionary prediction and using only the stoichiometry of $$\hbox {N}_5\hbox {AsF}_6$$ N 5 AsF 6 as a starting point, we were able to reveal the crystal structure of this high energy density material (HEDM). The $$\hbox {C}_{2V}$$ C 2 V symmetry of the $$\hbox {N}_5^+$$ N 5 + cation, as suggested from earlier investigations, is confirmed to be the symmetry adopted by this polymeric nitrogen within the crystal. This result gave full confidence in the validity of this crystal prediction approach. While stability of the $$\hbox {N}_5^+$$ N 5 + within the crystal is found to be driven by electronic considerations, the marginal stability of this HEDM is found to be related to a partial softening of its phonon modes.